“Impact of Educational Background on Academic Scores of Management Students: Case Study” - Morani, Renuka; Jain, Arjita (Gyan Management Journal, 2022)
Identifying the factors that influence academic performance of students is an essential part of educational research. Previous studies have documented the importance of personality traits, class attendance, parenting etc. This paper is aimed at evaluating the Influence of Stream of Graduation on Academic Score of Management Students. For this purpose, data was collected from a sample of 60 MBA students enrolled with a management institute of Navi Mumbai. Descriptive Statistics, One-way ANOVA and Tukey Honestly Significant Difference (HSD) Test was used for analysis. The first-year’s Academic Scores were taken as a measurement of Academic Performance of the MBA students. The results of the study revealed that there is no significant difference in Academic Scores of the MBA students from different educational background. The Levene’s Test revealed that the variance of all groups i.e B. Com, BMS and B.Sc. were equal. Tukey HSD test further confirmed that the academic scores of students having different background doesn’t significantly differ.